SEASONAL VARIATIONS IN MICRO MINERAL PROFILE OF LACTATING KANKREJ COWS (BOS INDICUS) - Lateef, A; Das, Hemen; Panchsara, HH; Sanap, MJ; Nilofar, Haque; Parasani, HR (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Present study reports seasonal variation in concentrations of copper (Cu), zinc (Zn), iron (Fe) and manganese (Mn) in different production groups of lactating Kankrej cows. The concentrations of Cu was significantly higher (p<0.05) in all the groups during summer season; while, Zn concentration was found to be significantly higher in winter as compared to rainy and summer seasons. Similarly, Fe concentrations in all the production groups were apparently lower in summer as compared to rainy and winter seasons. However, there was no definite pattern of variation in serum Mn concentration amongst the experimental groups. A comprehensive study is warranted on this aspect to evolve the correlations between blood concentrations of these microelements and productive performance of the breed.